A Single Surgeons Experience with Enhanced Recovery after Surgery: An Army of One. Issue 7 (July 2016) - Mosquera, Catalina; Koutlas, Nicholas J.; Fitzgerald, Timothy L.
The benefits of enhanced recovery after surgery (ERAS) have been demonstrated for multiple surgical procedures in high-volume programs. However, resources required for its implementation may be daunting to individual surgeons. Patients undergoing elective abdominal procedures from June 2013 to April 2015 by a surgical oncologist before and after the implementation of an ERAS protocol were reviewed. A total of 179 patients were included. The mean age of the patients was 63 years, and a majority of them were females (53.6%), white (61.5%), had a Charlson score of 0 to 2 (45.8%), and a Clavien complication grade of 0 to I (60.1%). The univariate analysis revealed that the ERAS protocol was associated with shorter length of stay (LOS) (6.2 vs 9.6 days), lower cost (21, 674 vs 30, 380), and lower mortality (0 vs 3.3%); P < 0.05. Differences were noted in LOS and costs for all procedures, the differences were the greatest for hepatic resection (3.8 vs 8.4 days and 16, 770 vs 28, 589), intestinal resection/stoma closure (4.8 vs 7.6 days and 18, 391 vs 22, 239), and other abdominal procedures (5.0 vs 10.8 and 17, 713 vs 30, 900); P < 0.05. The differences were less for patients undergoing procedures for which postoperative pathways were already in place such as pancreatic (9 vs 10.8 days and 30, 524 vs 34, 291) and colorectal (5.3 vs 6.5 days and 20, 733 vs 25, 150) surgeries. P > 0.05. An ERAS program can be instituted by an individual surgeon with the benefits of decreased LOS, cost, and mortality.